Effect of folinic acid on serum homocysteine, TNFα, IL-10, and HMGB1 gene expression in head injury model. (May 2021) - Tommy, Thomas; Islam, Andi A.; Hatta, Mochammad; Bukhari, Agussalim; Nasrullah,; Adhimarta, Willy; Aminuddin,; Zainuddin, Andi Alfian
Abstract: Background: Head injury or traumatic brain injury is the leading cause of mortality and morbidity. Many modalities of neuroprotection had been developed in brain injury but there was no much information regarding folinic acid's effect on neuroinflammation associated with homocysteine, TNFα, IL-10, and HMGB1. Objective: This study aimed to investigate whether folinic acid has improving effect on head injury model. Method: This study was done in the rat's head injury model using modified Marmarou weight drop model. Fifteen rats were randomized and grouped into 3 groups: Group A: Folinic acid (+), head injury (−); Group B: Folinic acid (−), head injury (+); Group C: Folinic acid (+), head injury (+). Folinic acid was administered intraperitoneally with a dose of 60 mg/m 2 . Blood samples were taken immediately after head injury (H0), 12 h (H12), and 24 h (H24) after head injury from the lateral vein of tail. Serum level of homocysteine, TNFα, and IL-10 were measured using ELISA, and HMGB1 gene expression was measured with Real-Time RT-PCR. Results: This study found serum level of homocysteine, TNFα, IL-10 and HMGB1 gene expression were markedly increased at all time points after head injury. Significantly lower level of serum homocysteine, TNFα, IL-10 and HMGB1 gene expression were found after 24 h treatment with folinic acid in group C compared to those in group B. Conclusion: Folinic acid may have anti-inflammatory properties in traumatic brain injury by inhibition of serum level of homocysteine, TNFα, IL-10 and HMGB1 gene expression. Highlights: An animal study of head injury model using modified Marmarou weight drop model. This three groups study with folinic acid treatment on head injury rats. Folinic acid has anti-inflammatory properties in traumatic brain injury model. Folinic acid inhibits serum level of homocysteine, TNFα, IL-10 and HMGB1expression.